CORRELATION OF PAIN INTENSITY AND HEALTH-RELATED QUALITY OF LIFE IN LUMBAR HERNIATED NUCLEUS PULPOSUS IN RSUD PROF. DR. MARGONO SOEKARJO - Raditya Bagas Wicaksono (Mandala Of Health, 2021)
Low back pain (LBP) was a health problem that disturbed clinically, socially, and economically. There was a worldwide and national increase of LBP every year. Both LBP and ischialgia were specific symptoms of herniated nucleus pulposus (HNP). Location of HNP mostly happened at L4-L5 and L5-S1 level. Chronic pain which existed in HNP patients could affect health-related quality of life. The aim of this study was to analyze correlation of pain intensity and quality of life in HNP patients in RSUD Prof. Dr. Margono Soekarjo in 2011-2013. This was a cross-sectional study with 26 subjects. Bivariable analysis was done by using Pearson correlation test with stratification based on body mass index. This study was approved by the Research Ethics Committee of FK Unsoed.. There was a significant correlation of pain intensity and quality of life (p<0,01) with negative direction and very strong correlation (r=-0,908) in normoweight respondents, and also strong correlation (r=-0,794) in obese respondents. There was also a significant correlation (p<0,001) with negative direction and very strong correlation (r=-0,852) in all respondents. Pain intensity has the strongest correlation with physical disability domain (r=-0,853). Higher pain intensity strongly impacts on the lower quality of life in lumbar HNP patients of RSUD Prof. Dr. Margono Soekarjo, and vice-versa.